Response of Diaphorina citri Kuwayama to Citrus suhuensis essential oil - Abd Hafidz, Hadhinah (2016)
Diaphorina citri Kuwayama (Hemiptera: Psyllidae) is an important worldwide pest of citrus, because of its ability to transmit phloem-limited bacteria in the genus Candidatus Liberibacter, that cause citrus greening disease or huanglongbing (HLB). D. citri was first reported in the Americas in Brazil during 1940s. Citrus greening disease has been reported in Malaysia since 1970. Besides, a recent report also showed that most of the cultivated citrus varieties in Peninsular Malaysia, Sabah and Sarawak have been infected with citrus greening disease. The occurance of huanglongbing disease is still little available information regarding this disease in Malaysia. Until now, there is no successful treatment either by using pesticides or antibiotics, therefore to avoid and destruct of infected trees are the only practical method applied today to prevent disease spread in the orchards. This experiment was conducted to examine the response of D. citri towards ten different combination of treatment consist of control, 12.5μl, 25μl, 50μl, and 100μl of C. suhuensis essential oil by using Y- tube olfactometer. Distilled water were used as a control in this experiment. 10 replication for both male and female were prepared in order to observe the responses of D. citri toward different combination of treatmentsAmong these volume of treatments, both male and female gave positive responses towards the 12.5μl treatment and this suggest that D. citri were able to be attracted even at a lower volume of olfactory stimuli. The result were discussed in term of mean response time and percentage of responding between male and female D. citri. Based on the result obtained, female D. citri showed vigorous responses over male D. citri.